2021
DOI: 10.3390/insects12080680
|View full text |Cite
|
Sign up to set email alerts
|

Using Matching Traits to Study the Impacts of Land-Use Intensification on Plant–Pollinator Interactions in European Grasslands: A Review

Abstract: Permanent grasslands are suitable habitats for many plant and animal species, among which are pollinating insects that provide a wide range of ecosystem services. A global crisis in pollination ecosystem service has been highlighted in recent decades, partly the result of land-use intensification. At the grassland scale, however, the underlying mechanisms of land-use intensification that affect plant–pollinator interactions and pollination remain understudied. In this review, we first synthesise the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 91 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…Depending on their geographic location, environmental conditions and the type and stocking rate of herbivores, pastures could be dominated by grazing-tolerant plant species with either generalist or specialist floral functional traits. A recent review has highlighted the lack of data on the effect of grazing on floral traits, with the available research indicating that generalist flowers could be favoured [31]. However, some studied reveal that Fabaceae, which have quite specialized flowers, are often dominant in intensive pastures throughout Europe (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their geographic location, environmental conditions and the type and stocking rate of herbivores, pastures could be dominated by grazing-tolerant plant species with either generalist or specialist floral functional traits. A recent review has highlighted the lack of data on the effect of grazing on floral traits, with the available research indicating that generalist flowers could be favoured [31]. However, some studied reveal that Fabaceae, which have quite specialized flowers, are often dominant in intensive pastures throughout Europe (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring weed floral phenotypes in more detail by considering supplementary floral traits such as scents or colours and by studying weed pollinators could also help to understand the differences we discovered between the flowers of weeds and grassland species flowers (Junker and Parachnowitsch 2015). Moreover, studying plant–pollinator trait matching could help to better understand these results (Goulnik et al 2021). At last, these observed discrepancies could be related to our datasets, limited in the number of species and not necessarily representative of the two floras being compared.…”
Section: Discussionmentioning
confidence: 99%
“…Since we found that floral traits are linked to CSR strategies, which are modified by agricultural practices (Kazakou et al 2016), it is possible that weed management could also affect the available floral resources in agroecosystems. High‐intensity land use in grasslands is already known to shape floral resources by homogenising floral traits, inducing changes in flower colour, nectar tube depth or resource production (Goulnik et al 2021). Diversifying agricultural practices at the landscape level to increase the functional diversity of weeds could contribute to diversify the flower resource for pollinators (Fründ et al 2010) as well as provide the numerous other ecosystem services expected from weeds, such as producing food resources for livestock (Genty et al 2023a) and natural enemies (Serée et al 2023) but also supporting processes contributing to soil fertility, such as decomposition (Bopp et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Plant–plant and plant–pollinator interactions depend, at least to some degree, on the functional trait matching between partners (i.e. Goulnik et al, 2021). Anthropogenic change can alter this functional fit between partners by either changing the composition and abundance of species within a community (as discussed above) or by creating new selection pressures or induce phenotypic plasticity, resulting in floral and pollinator trait changes (Descamps et al, 2021; Parra‐Tabla et al, 2021; Thompson et al, 2021).…”
Section: Key Questionsmentioning
confidence: 99%